Phage-Like Streptococcus pyogenes Chromosomal Islands (SpyCI) and Mutator Phenotypes: Control by Growth State and Rescue by a SpyCI-Encoded Promoter - Scott, Julie; Nguyen, Scott V.; King, Catherine; Hendrickson, Christina G.; Mcshan, William M. (Frontiers in Microbiology, 2012)
We recently showed that a prophage-like Streptococcus pyogenes chromosomal island (SpyCI) controls DNA mismatch repair (MMR) and other repair functions in M1 genome strain SF370 by dynamic excision and reintegration into the 5’ end of mutL in response to growth, causing the cell to alternate between a wild type and mutator phenotype. Nine of the sixteen completed S. pyogenes genomes contain related SpyCI integrated into the identical attachment site in mutL, and in this study we examined a number of these strains to determine whether they also had a mutator phenotype as in SF370. With the exception of M5 genome strain Manfredo, all demonstrated a mutator phenotype as compared to SpyCI-free strain NZ131. The integrase gene (int) in the SpyCIM5 contains a deletion that rendered it inactive, and this deletion predicts that Manfredo would have a pronounced mutator phenotype. Remarkably, this was found not to be the case, but rather a cryptic promoter within the int ORF was identified that ensured constitutive expression of mutL and the downstream genes encoded on the same mRNA, providing a striking example of rescue of gene function following decay of a mobile genetic element. The frequent occurrence of SpyCI in the group A streptococci may facilitate bacterial survival by conferring an inducible mutator phenotype that promotes adaptation in the face of environmental challenges or host immunity.